A Fiber-Coupled Self-Mixing Laser Diode for the Measurement of Young’s Modulus - Ke Lin; Yanguang Yu; Jiangtao Xi; Huijun Li; Qinghua Guo; Jun Tong; Lihong Su (Sensors, 2016)
This paper presents the design of a fiber-coupled self-mixing laser diode (SMLD) for non-contact and non-destructive measurement of Young’s modulus. By the presented measuring system, the Young’s modulus of aluminum 6061 and brass are measured as 70.0 GPa and 116.7 GPa, respectively, showing a good agreement within the standards in the literature and yielding a much smaller deviation and a higher repeatability compared with traditional tensile testing. Its fiber-coupled characteristics make the system quite easy to be installed in many application cases.